Public organizations from institutional perspectives and dinamic capabilities (Revista Científica Compendium, 2018)
Public organizations are subject to constant legitimation and acceptance process by the society. In order to deal with this, the development and evolution of these mechanisms require fostering adequacy and/or adaptation capabilities. Such considerations, marked the interest of this essay to establish a set of possible links between the institutional Theory and the dynamic-capability theory specifically perceived in the approach to a citizen-oriented public management model. The pointed-out appreciations underlay in the role performed by public organizations where necessarily must coexist both adaptability and legitimation actions and processes, stating the governance as, not only an emerging expression of those process, but as a more efficient way to the public function execution.
Keywords: Public management; governance; institutional theory; dynamic capabilities